PENINGKATAN STATUS GIZI BALITA DENGAN PROMOTIF KIE DAN SKRINING DI MASA PANDEMI COVID 19 MELALUI LAYANAN KETUK PINTU - Mella Yuria R.A.; Royani Chairiyah; Legina Anggraeni (Bajang Institute, 2022)
Nutritional status is very influential on the growth and development of toddlers and affects the intelligence of toddlers. An imbalance in nutritional intake can increase the fatality of COVID-19 infection. The limited service at the Posyandu has an impact on maternal and under-five health services and hampers the monitoring of under-five growth and development. Cadres take the initiative to monitor the growth of toddlers independently through home visits while still complying with the Covid-19 prevention health protocol. This community service aims to monitor the nutritional status of children under five and early detection of nutritional problems. The method used is by screening the nutritional status of children under five with anthropometric measurements of BB/TB then given IEC education. The result of this activity is that 5.71% of children under five are malnourished. This is because apart from parenting factors, it is also due to the fact that during the pandemic, parents' income has decreased so that the pattern of feeding their toddlers is only based on their child's preferences without paying attention to balanced nutritional food patterns